PSYCHO-EDUCATIONAL FOUNDATION OF TEACHING ENGLISH GRAMMAR TO PRIMARY SCHOOL CHILDREN - Natalia Leonidovna Moskovskaya; Irene Valerievna Zhabina (Вестник Северо-Кавказского федерального университета)
This article deals with the problem of taking into account the psychophysiological qualities of children in pri- mary school during the process of teaching English grammar.